Metafora dalam Dinamika Harga Saham: Metaphor in Dynamic Stock Price - Yohanis Sanjoko; Icuk Prayogi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study is about how stock prices are perceived by capital market players. Lakoff and Johnson's theory of conceptual metaphor is used to overcome the problem. The data sources are online mass media and stock conversation groups on Telegram because they are considered as the representatives of metaphor use of stock prices. According to data analysis, there is no non - metaphorical expression about stock prices. The dy- namic of stock prices covers some aspects, including orientational metaphor, dualism and three - ism con- cepts, stock as object and subject of battle, moving stock prices, and ontological metaphors of stock prices.